Interleukin-10 polymorphisms (rs1800871, rs1800872 and rs1800896) and periodontitis risk: A meta-analysis. (January 2019) - Yang, Shu-Liang; Huang, Shi-Jie
Highlights: Interleukin-10 (IL-10) is a key suppressive cytokine in the pathogenesis of periodontitis. The IL-10 rs1800871 and rs1800872 polymorphisms may confer an increased risk of periodontitis only in Latin American populations. No significant association was observed between rs1800896 and periodontitis. Abstract: Objective: The objective of this meta-analysis was to assess the association between three interleukin-10 ( IL-10 ) promoter single nucleotide polymorphisms (rs1800871, rs1800872, and rs1800896) and periodontitis risk. Methods: A systematic search was conducted in PubMed, Embase, and China National Knowledge Infrastructure databases and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Results: Twenty-six studies met the inclusion criteria. The pooled analysis showed that rs1800871 was associated with an increased periodontitis risk under dominant model (CT + TT vs. CC: p = 0.004, OR = 1.79, 95% CI: 1.21–2.65) in Latin American populations but not in Asian (CT + TT vs. CC: p = 0.229, OR = 0.81, 95% CI: 0.58–1.14) and Caucasian (CT + TT vs. CC: p = 0.910, OR = 1.02, 95% CI: 0.75–1.39) populations. Similarly, rs1800872 conferred an increased risk of periodontitis only in Latin American populations (CA + AA vs. CC: p = 0.012, OR = 2.32, 95% CI: 1.20–4.47; A allele vs. C allele: p = 0.001, OR = 1.61, 95% CI: 1.22–2.14). No significant association was observed between rs1800896 and periodontitis risk. Subgrouping data according to periodontitis type revealed that rs1800872 was associated with both chronic periodontitis (A allele vs. C allele: p = 0.011, OR = 1.72, 95% CI: 1.13–2.62) and aggressive periodontitis (A allele vs. C allele: p = 0.038, OR = 1.32, 95% CI: 1.02–1.72). Conclusion: The studies reviewed support that the IL-10 rs1800871 and rs1800872 polymorphisms may represent a potential genetic biomarker for periodontitis risk in Latin American populations.